2015
DOI: 10.1242/dev.097113
|View full text |Cite
|
Sign up to set email alerts
|

Innexin7a forms junctions that stabilize the basal membrane during cellularization of the blastoderm in Tribolium castaneum

Abstract: In insects, the fertilized egg undergoes a series of rapid nuclear divisions before the syncytial blastoderm starts to cellularize. Cellularization has been extensively studied in Drosophila melanogaster, but its thick columnar blastoderm is unusual among insects. We therefore set out to describe cellularization in the beetle Tribolium castaneum, the embryos of which exhibit a thin blastoderm of cuboidal cells, like most insects. Using immunohistochemistry, live imaging and transmission electron microscopy, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…This led to some extrapolation in the literature that innexin channels may also contain hexameric hemichannels and dodecameric junction channels like connexin [29][30][31][32]. On the other hand, it has also been reported that invertebrate gap junction channels are larger than vertebrate junction channels [12][13][14][15]20].…”
Section: Discussionmentioning
confidence: 99%
“…This led to some extrapolation in the literature that innexin channels may also contain hexameric hemichannels and dodecameric junction channels like connexin [29][30][31][32]. On the other hand, it has also been reported that invertebrate gap junction channels are larger than vertebrate junction channels [12][13][14][15]20].…”
Section: Discussionmentioning
confidence: 99%
“…Nv-coronin ’s functional annotation is consistent with a role in cellularization, as it is predicted to interact with both the microtubule and actin cytoskeletons, both of which are crucial for mitosis and cell formation. While Innexin1 is most well known as a crucial component of gap junctions and a role in the nervous system [57], a role for at least one Innexin in cellurization has been demonstrated in the beetle Tribolium [58], suggesting that the full potential of these proteins in regulating cellular processes has not been fully explored.…”
Section: Resultsmentioning
confidence: 99%
“…The different requirement for Fog signaling during cellularisation in Drosophila and three insects we have studied may be linked to variations in the modes of cellularisation. The formation of a high-columnar blastoderm, which has been well studied in Drosophila, is an exception among insects and even among flies (Bullock et al, 2004;van der Zee et al, 2015). In many insects, cellularisation generates a blastoderm of cuboidal cells, while some insects initially form individual cells that then migrate to form a continuous epithelium (Ho et al, 1997;Nakamura et al, 2010).…”
Section: Fog Signaling Has Tissue Wide Functions In the Blastoderm Anmentioning
confidence: 99%
“…However, the way in which this may occur at a mechanistic level is a completely open question. The discovery of special Innexin-based cell junctions that are essential for cellularisation in Tribolium, but do not exist in Drosophila, highlights the potential diversity in mechanisms underlying cellularisation in different insects (van der Zee et al, 2015). Thus, as with the spreading of the serosa, future work is required to uncover the mechanism of Fog signaling during blastoderm formation in Tribolium and other insects.…”
Section: Fog Signaling Has Tissue Wide Functions In the Blastoderm Anmentioning
confidence: 99%
See 1 more Smart Citation